Tissue engineering of corneal stroma via melt electrowriting. (5th August 2021) - Gao, Qi; Xie, Jiajun; Salero, Enrique; Nuñez del Prado, Zelmira; Hutmacher, Dietmar W.; Ye, Juan; De Juan‐Pardo, Elena M.; Sabater, Alfonso L.; Perez, Victor L.
Abstract: The cornea serves as the main refractive component of the eye with the corneal stroma constituting the thickest component in a stratified layered system of epithelia, stroma, and endothelium. Current treatment options for patients suffering from corneal diseases are limited to transplantation of a human donor cornea (keratoplasty) or to implantation of an artificial cornea (keratoprosthesis). Nevertheless, donor shortage and failure of artificial corneas to integrate with local tissue constitute important problems that have not been yet circumvented. Recent advances in biofabrication have made great progress toward the manufacture of tailored biomaterial templates with the potential of guiding partially or totally the regeneration process of the native cornea. However, the role of the corneal stroma on current tissue engineering strategies is often neglected. Here, we achieved a tissue‐engineered corneal stroma substitute culturing primary keratocytes on scaffolds prepared via melt electrowriting (MEW). Scaffolds were designed to contain highly organized micrometric fibers to ensure transparency and encourage primary human keratocytes to self‐orchestrate their own extracellular matrix deposition and remodeling. Results demonstrated reliable cell attachment and growth over a period of 5 weeks and confirmed the formation of a dense and highly organized de novo tissue containing collagen I, V, and VI as well as Keratocan, which resembled very closely the native corneal stoma. In summary, MEW brings us closer to the biofabrication of a viable corneal stroma substitute.